Piezoelectric-triboelectric hybrid nanogenerator based on tough, stretchable BaTiO3 doped antibacterial hydrogel for self-powered sensors - Runi Hou; Lijian Xu; Maolin Yu; Zengmin Tang; Bin Zhou; Qiao Zhang; Na Li; Jianxiong Xu (Supramolecular Materials)
The pursuit of nanogenerators with superior electrical output performance is crucial for advancing high-performance self-powered sensors, yet enhancing their performance through effective strategies remains a formidable challenge. Herein, a kind of piezoelectric-triboelectric hybrid nanogenerator (PTENG) utilizing a tough, stretchable BaTiO3 doped hydrogel was developed. To this end, a functional hydrogel of oxidized sodium alginate (OSA) crosslinked poly(acrylic acid-co-acrylamide) (P(AA-co-AM)) in the presence of BaTiO3 (BTO) nanoparticles was initially prepared and then immersed in FeCl3 solution to form OSA/P(AA-co-AM)/Fe3+-BTO (O/P/Fe-BTO) hydrogels. Due to the multiple interaction (such as dynamic Schiff base cross-linking bond, metal coordination and hydrogen bonding), along with the synergistic contributions of each component, the as-prepared O/P/Fe-BTO hydrogels displayed outstanding mechanical property (tensile stress of 2.14 MPa, tensile strain of 876 %, toughness of 9.96 MJ/m3), good conductivity (0.14 S/m) and excellent antibacterial activity. Subsequently, a kind of PTENG was constructed by employing the O/P/Fe-BTO hydrogels as electrode materials. Leveraging both triboelectric and piezoelectric effects, the PTENG demonstrated excellent electrical output performance (open-circuit voltage of 222 V and short-circuit current of 5.35 μA). As a practical demonstration, the application of PTENG in self-powered strain and tactile sensors was demonstrated, manifesting their promising potential in self-powered sensing system. Overall, this work represents a noteworthy advancement in the domain of self-powered flexible electronics, with the potential for application in a wide range of complex scenarios.